Numerical implementation of rock bolts with yield and fracture behaviour under tensile-shear load. (September 2022) - Sun, Bing-jun; Liu, Quan-wei; Li, Wei-teng; Yang, Xiu-zhang; Yang, Bo; Li, Ting-chun
Highlights: A numerical model of rock bolt tension-shear coupling that can realize bearing-yield-breaking behaviour was developed. An indoor tensile-shear test of rock bolts was conducted to verify the new numerical model. In the case of roadway support, the phenomenon of yielding and breaking of rock bolts is reproduced. Abstract: To realize the numerical analysis of rock bolt bearing-yield-fracture under tension-shear coupling and to provide an effective means for supporting the design of roadways or tunnels, a new numerical model was developed to analyse the tension-shear coupling fracture behaviour of rock bolts in engineering rock masses. Based on the study of the mechanical behaviour of rock bolts under tensile-shear coupling load, the mechanical criterion and constitutive model of the yield and fracture of rock bolts were proposed, and the secondary development of the FLAC 3D platform was realized. At the same time, self-developed equipment was used to conduct the rock bolt tensile shear test. By comparing the numerical simulation results with the experimental results, we determine that the maximum difference in the shear displacement of the rock bolt does not exceed 2 mm during the yielding and breaking of the rock bolt, and the percent difference was approximately 3% and 10%, respectively. In the field of engineering, this result is generally considered acceptable. Using the numerical model we proposed, a numerical simulation experiment was conducted on the rock bolt support design of a coal mining roadway in engineering practice. The results show that under the original support scheme, a large amount of rock bolt tensile-shear failure occurs at the coal-rock interface, which makes the original support scheme unable to meet the engineering requirements with tensile-shear coupling failure tendency. In this regard, we adopted the support method of grouting anchorage at the interface of coal and rock. The results show that the deformation of the roadway surrounding rock has been effectively controlled.